Phylogrouping, Serogrouping, Virulence Factors and Carbapenemase Genes among Carbapenemase-Producing Escherichia Coli From Urinary Tract Infections - Ahmed A. Mhawesh; Daniah Muneam Hamid; Abdolmajid Ghasemian (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Escherichia coli is among major nosocomial pathogens causing urinary tract infections(UTIs). The emergence of carbapenem- resistant strains is a major concern regarding the UTI treatment. Thesubjective of this study included assessment of genetic relation and screening of virulence factors amongcarbapenemase producing E. coli from UTI.Materials and methods: Three-Hundred E. coli isolates were enrolled. Antibiotic susceptibility test wasconducted by disk diffusion as provided by clinical and laboratory standards institute (CLSI). Carbapenemaseproduction and presence of bla OXA-48, bla KPC, bla NDM, bla VIM and bla IMP genes were evaluated by PCRtechnique. Virulence factors genes were also screened by PCR technique. Genetic relation of isolates wasimplemented using phylogrouping and serogrouping.Results: Of 300 isolates, 11 (3.66%) of them were resistant to carbapenems (CR-E. coli). Imipenemminimum inhibitory concentration ranged 4-128µg/ml. The bla OXA-48 and blaIMP genes were co-existed inthree (1%) isolates (imipenem MIC: 64-128µg/ml), but the bla KPC, bla NDM and bla VIM were not amplified.Predominant virulence genes included iutA (n=293, 97.66%), fyuA (n=256, 85.33%), inh (n=249, 83%), traT(n=247, 82.33%), pap? (n=96, 32%), fimH (n=93, 31%), csgA (n=92, 30.66%). All the CR-E. coli containedthe iutA, fyuA, traT, papII, fimH and csgA genes. O1 (32%), O16 (15%) and O25 (7%) serogroups werepredominant and 6/11, 4/11 and 1/11 of CR-E. coli belonged to O1, O25 and O75 serogroups, respectively.Among eleven CR-E. coli isolates, nine of them were belonged to the B2 phylogroup and two isolates werebelonged to B1 phylogroup.Conclusion: CR-E. coli contained the blaIMP and blaOXA-48 genes and predominantly O1 serogroup. Highrate of virulence factors among CR-E. coli from UTI is a concern in Baghdad hospitals. The spread ofisolates with resistance to last-line antibiotics must be controlled.